2016
DOI: 10.1080/10253890.2016.1174847
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative stress and autonomic dysregulation in a community sample

Abstract: Whether cumulative stress, including both chronic stress and adverse life events, is associated with decreased heart rate variability (HRV), a non-invasive measure of autonomic status which predicts poor cardiovascular outcomes, is unknown. Healthy community dwelling volunteers, (N= 157, mean age 29 years) participated in the Cumulative Stress/Adversity Interview, (CAI) a 140-item event interview measuring cumulative adversity including major life events, life trauma, recent life events and chronic stressors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 81 publications
3
14
0
Order By: Relevance
“…There are several findings from other authors that confirm the results of the present study. Our results correspond with the results of the study of Lampert et al 73 that showed that total cumulative stress score and cumulative adverse life events were all inversely associated with standard deviation of NN intervals (SDNN), which is linked to the parasympathetic tone. High-frequency variability may be significantly reduced in the patients with depression, indicating that depressive patients have an aberration in the parasympathetic nervous system activity.…”
Section: Discussionsupporting
confidence: 92%
“…There are several findings from other authors that confirm the results of the present study. Our results correspond with the results of the study of Lampert et al 73 that showed that total cumulative stress score and cumulative adverse life events were all inversely associated with standard deviation of NN intervals (SDNN), which is linked to the parasympathetic tone. High-frequency variability may be significantly reduced in the patients with depression, indicating that depressive patients have an aberration in the parasympathetic nervous system activity.…”
Section: Discussionsupporting
confidence: 92%
“…The ANS and symptoms of gastroparesis can be altered by many factors, including age, gender, disease, stress, and medications. We hypothesize that autonomic dysfunction plays a role in the gastric motility and symptom severity of patients with gastroparesis and CUNV.…”
Section: Introductionmentioning
confidence: 99%
“…A unique strength of this research is its focus on daily hassles and minor stressors, which are recognized as important to overall health but have not been thoroughly studied in the context of addiction and relapse. Cumulative stressful life events and chronic stress are associated with decreased cardiac autonomic function in healthy adults (Lampert et al, 2016). Among patients with Crohn’s disease, daily hassles are associated with increased disease activity, reduced quality of life, and lower economic status (Sarid et al, 2018).…”
Section: Discussionmentioning
confidence: 99%